Effect of physical exercise using α-lipoic acid (ALA) and eicosapentaenoic acid (EPA) on physical fitness, recovery, and performance in young weightlifters - Hayder Jabbar Abd (Universidad de Murcia, 2023)
Article accepted. The article will be published here soon. Pending final quality checks.